1974
DOI: 10.1002/bjs.1800610407
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and prevention of wound infection in appendicectomy

Abstract: A study at the Reading District Hospitals on 451 consecutive patients undergoing appendicectomy through grid‐iron incisions sought to determine factors influencing wound infection and the effects of a prophylactic wound‐spraying procedure. Wound infection increased with the severity of appendicular inflammation and was well correlated with the degree and nature of bacterial contamination at the time of wound closure1. The infection rate was reduced by about one‐half when either an aerosol dry‐powder formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
2
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 11 publications
5
41
2
1
Order By: Relevance
“…E. coli was the leading microorganism in the appendeceal lumen, and which translocate to MLN. In the literature, it has been reported that E. coli, and Streptococcus are the commonest organisms involved in an inflamed appendix [4,5,17]. The relationship between translocation and tissue injury score was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli was the leading microorganism in the appendeceal lumen, and which translocate to MLN. In the literature, it has been reported that E. coli, and Streptococcus are the commonest organisms involved in an inflamed appendix [4,5,17]. The relationship between translocation and tissue injury score was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…5,[9][10][11][12] Most authors have reported rates of about 5% for wound infection and 10% for postoperative intra-abdominal abscess. 5,[9][10][11][12][14][15][16][17][18] Although some reports (both adult and pediatric, often combined) indicate that some form of antibiotic prophylaxis will diminish the incidence of both complications, 35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] others claim it makes no difference. 5,23,24,[27][28][29][30][31][32][33]36,[51][52][53][54] In our series, each ruptured appendix at operation had an obvious perforation confirmed by histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…The wound Penrose drain [3] or one half-inch gauze pack [4] and/or antibiotic powder [5][6][7][8][9][10][11][12] (ampicillin, 1977-1981; cefoxitin 1982-1995) were all placed in the subcutaneous space. If the infant or child was allergic to penicillin, no antibiotic powder was placed in the wound and intravenous clindamycin (or metronidazole) and gentamicin were used.…”
Section: Methodsmentioning
confidence: 99%